Influence of spatial soil variability on productivity and physiological quality of soybean seeds - Castellanos, César Iván Suárez; Gadotti, Gizele Ingrid; Meneghello, Geri Eduardo; Cavalcante, Jerffeson Araujo; Pinheiro, Romário de Mesquita (Revista Agrogeoambiental, 2022)
Seed production fields present spatial and temporal variability in the physical and chemical characteristics of the soil, thus influencing the yield and quality of the produced seeds. The objective of this study was to characterize the spatial variability in soil attributes providing physiological quality and productivity in soybean seeds in two commercial production fields, aiming to define areas of agronomic management. The experiment was carried out in the 2014/15 and 2015/16 crop seasons in a 100×100 m grid. Soil sampling was performed at a depth of 0-200 mm with a 75×75 m grid. The soybean samples were collected at the end of the 2014/15 crop season. Therefore, soil analysis was determined only in the 2014/15 crop season. The plants' agronomic characteristics and the productivity and physiological quality of produced seeds were determined for both crop seasons. Thus, it was concluded that the study site presented spatial variability in soil characteristics, phosphorus content, organic matter, cation exchange capacity, sand, and clay content, and the agronomic characteristics of soybean plants cv. BMX Desafio RR, including plant height, number of nodes per plant, number of pods with three seeds, number of pods with seeds, number of seeds per plant, seed weight per plant, seed weight per linear meter, productivity, and germination. Seed productivity showed a strong spatial dependence, while germination showed a moderate spatial dependence. Three management zones were determined according to the spatial distribution of the results obtained.